ANALISIS PENGARUH KEMISKINAN TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI SUMATERA SELATAN TAHUN 2012-2021 - Muhammad Rafi Zain; Umar Hariyadi; Muhammad Athaya Kailashandy; Isvan Aditya Nugraha; Firdaus Aulia Fauzi; Deris Desmawan (Universitas Veteran Bangun Nusantara, 2023)
Poverty and economic growth in South Sumatra Province need attention from the government of South Sumatra, if there is a correlation between the examined variables. The variable being tested is the independent variable, namely poverty and the dependent variable, namely economic growth. This examination utilizes the quantitative approach and relies on secondary data sources in the form of information from the Central Bureau of Statistics. The results obtained after being tested multiple linear regression analysis, namely poverty, found no relevant effect on economic growth. If the poverty rate increases, then it cannot be determined that the economic growth rate will decrease in South Sumatra Province.